Avaliação dos minerais séricos e da função hepática de frangos de corte intoxicados experimentalmente com aflatoxina e submetidos a diferentes concentrações de montmorilonita sódica na dieta - Franciscato, Carina (2006)
Aflatoxins are toxic metabolites produced by Aspergillus flavus, A. parasiticus and A. nominus genus fungi and can occur as natural contaminants of foods. Aflatoxins cause a variery of effects in poultry, including poor performance, liver pathology, immunosupression and changes in relative organ weights. Determination of biochemical toxic effects of aflatoxins is important for diagnosis of aflatoxicosis in broiler chickens. The aim of this research was to evaluate the serum mineral and the hepatic function of broiler chicken experimentally intoxicated using 3 ppm of aflatoxin and submitted to different concentrations of clay sodic montmorilonite on the diet. In this study were used 720 Cobb s broiler chickens that were divided in 6 treatments from 1º to 42º day of life: (T1) control: normal diet; (T2) diet with 3 ppm of aflatoxin; (T3) diet with 0,25% sodic montmorilonite; (T4) diet with 3 ppm of aflatoxin + 0,25% sodic montmorilonite; (T5) diet with 0,50% sodic montmorilonite; (T6) diet with 3 ppm of aflatoxin + 0,50% sodic montmorilonite. The treatment T2 showed significantly (P<0.05) decreased in serum concentrations of total protein, albumin, globulins and aspartate aminotransferase (AST); there was significant decreased on uric acid in treatment T4; in treatment T6 there was significant decrease in serum phosphorus levels; the serum calcium and magnesium were not affected by treatments. The aflatoxin in the diet (3ppm) causes changes in the hepatic function of broiler chickens. The use of sodic montmorilonite is effective in preventing the toxic effects of aflatoxins. However, addition of 0,50% sodic montmorilonite in the diet causes decrease in phosphorus levels.